ANALISIS KEBUTUHAN: PENGEMBANGAN E-MODUL MENULIS PROPOSAL PENELITIAN BERBASIS CONTEXTUAL TEACHING AND LEARNING - Rofii, Afif; Ramli, Ramli (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
In the development of educational models, conducting a needs analysis is crucial to identify existing knowledge and learning gaps among users. This is to ensure that the developed model aligns to their specific needs and offers practical benefits. This research is part of a broader Research and Development entitled A Contextual Teaching and Learning-Based E-Module for Writing Research Proposals. As a part of quantitative approach, this needs analysis utilizes the survey method. A questionnaire designed with a Likert scale serves as the instrument in collecting data. The quantitative data are scores obtained from the questionnaire responses. The descriptive statistic method was used to analyze the data by aligning the obtained scores with predetermined parameters signifying the level of need. The results suggested that the pre-writing stage assigned the students with nine questions at a very high (VH) category and one question within the high (H) category. Similarly, during the writing stage, students were administered to 60 questions divided into 23 questions at the very high (VH) category and 37 questions at a high (H) category. Finally, in the post-writing stage, students were assigned to ten questions comprising of two very high (VH) category questions and eight questions within the high (H) category. As a result, these findings unequivocally demonstrate that students require all the information encompassed within the needs analysis questionnaire throughout the pre-writing, writing, and post-writing phases of writing research proposal. Keywords: Needs analysis, E-Module for Writing Research Proposal, Contextual Teaching and Learning (CTL)